2003
DOI: 10.1177/1043659603257162
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Support and Acculturation on Postpartum Depression in Mexican American Women

Abstract: Postpartum depression was studied in 66 multiparous Mexican American women using a prospective longitudinal design. Interviews were conducted at 34 to 36 weeks prenatally and 4 to 6 weeks postpartum. Women expressing prenatal depression were more likely to continue to experience depression postpartum. Other predictors included a high need for postpartum support, specific support network characteristics, acculturation, and poor quality relationships within the family. It is important for the health care provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 41 publications
6
96
1
8
Order By: Relevance
“…28,29 Although a solid body of work focuses on Latinas and mental health, fewer studies focus on mental health in pregnant Latinas exposed to intimate partner violence. Depression, ranging from 38% to 51% among pregnant Latinas, 30,31 is the most common mental health outcome associated with intimate partner violence. There is also evidence of an association between intimate partner violence and posttraumatic stress disorder (PTSD), [32][33][34][35][36][37] but little is known about PTSD rates among pregnant Latinas or differences in depression or PTSD and exposure to intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Although a solid body of work focuses on Latinas and mental health, fewer studies focus on mental health in pregnant Latinas exposed to intimate partner violence. Depression, ranging from 38% to 51% among pregnant Latinas, 30,31 is the most common mental health outcome associated with intimate partner violence. There is also evidence of an association between intimate partner violence and posttraumatic stress disorder (PTSD), [32][33][34][35][36][37] but little is known about PTSD rates among pregnant Latinas or differences in depression or PTSD and exposure to intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…The rates may double or triple when other risk factors are present, such as poverty, relocation, or medical problems during pregnancy [2][3][4][5]. As alarming as these rates may seem, they may underestimate the prevalence of PD, since up to 50% of all postnatal depressed cases go undetected and untreated [6].…”
Section: Introductionmentioning
confidence: 99%
“…One study found up to 35% of the African-American female population reporting PPD symptoms (Moses- Kolko & Roth, 2004) while another found 38% of Mexican-American participants with PPD (Martinez-Schallmoser et al, 2003). Symptoms begin about two weeks after delivery and include a depressed mood, anxiety, short temper, feeling hopeless, lack of interest in the newborn baby or other activities in general, decreased appetite, lower levels of concentration/ focus, feelings of guilt, depressed mood, and sleeplessness (United States Department of Health & Human Services, 2005).…”
Section: Introductionmentioning
confidence: 99%